Holokaustas Raseinių apskrityje: Nemakščių valsčiaus žydų žūtis - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2010)
This third article (out of three) on the Holocaust in the summer of 1941 in the north-western part of Raseiniai District continues a series of articles about the destruction of Jewish communities, the two other articles being about the Kražiai and Viduklė rural districts (see Genocide and Resistance, 2009 No. 2(26) and 2010 No. 1(27). The Nemakščiai Jewish community, which mainly accumulated capital from selling horses, was the richest of the neighbouring shtetls (i.e. the towns with predominantly Jewish population). Among the district and rural district centres, Nemakščiai in 1940 was the only settlement with a majority of Jews (population of around 650). The only neighbouring locations with a larger Jewish population were the towns of Raseiniai, Jurbarkas, and Kelmė. During the Soviet occupation of 1940–1941, underground activities were taking place in this rural district. At the beginning of the war between Germany and the Soviet Union and the June 1941 Uprising, prior to the Nazi Wermacht entering Nemakščiai, members of the underground movement organised themselves into an independent unit for the protection of inhabitants and their property. The rural district suffered losses (the church was burnt down) and there were victims on both warring sides. In revenge for German soldiers killed by the Red Army, the Nazis killed several hostages—eight Lithuanian men from the villages of Švendūna and Geidėnai and another three from the village of Očikiai. The Nemakščiai Rural District, which was in a strategic location at the crossing of the road and rail connecting Tilsit and Riga with Žemaičiai Road, was controlled by the Skaudvilė Commandant (Tauragė District) and a unit of the Tilsit Operational Squad (later—Operational Group A, which carried out the massacre of Jews in Lithuania). On 26 and 27 June 1941, men from the self-protection unit of the Nemakščiai Rural District were taken to Skaudvilė (their numbers were reduced by the murder of the hostages), given instructions, and armed with rifles. Remnants of this squad, which acquired the informal status of a supporting police force and was supplemented with recruits, aided the Germans stationed in the rural district to carry out the neutralisation, discrimination, and isolation of the Jews.